The new global threat : severe acute respiratory syndrome and its impacts - Koh, Tommy T. B. (Tommy Thong Bee), 1937-; Plant, Aileen J.; Lee, Eng Hin, 1947- (World Scientific Pub. Co., 2003)
A disease that has given globalization a bad name, Severe Acute Respiratory Syndrome (SARS), has plagued no fewer than 30 areas in recent months. In this book, for the first time, leading scientists and researchers converge to shed light on the impacts and implications of this new global threat. Collected together within the volume are more than 20 articles that discuss and examine the SARS outbreak from wide-ranging perspectives - political, social, economic and health. The reader is given insights into how the SARS outbreak has altered public and political understanding of the threat of infec.